Role of liver function tests among pregnant women with respect to feto-maternal outcome in third trimester: an analytical cross-sectional study - Singh, Sapna; Yadav, Priyanka; Lal, Pavika; Verma, Pratima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Liver disease occurs in approximately 3% of pregnant women so it has adverse effect on feto-maternal outcome. Diseases specifically related to pregnancy are intra-hepatic cholestasis of pregnancy, acute fatty liver of pregnancy, abnormal liver function with preeclampsia, HELLP syndrome and hyperemesis gravidarum. Aim was to determine prevalence of liver disease in pregnancy and the impact of abnormal liver function tests on feto-maternal outcome Methods: It was an analytical cross-sectional study conducted in the department of obstetrics and gynecology, UISEMH, GSVM Medical College, Kanpur for a period of 2 years. All antenatal patients between the ages of 18-40 years who presented with abnormal liver function tests in third trimester were enrolled. Socio demographic and detailed clinical history was taken from all such patients and they were followed till delivery for feto-maternal outcome. Results: Hypertensive disorders in pregnancy were the most common cause of abnormal liver function tests in pregnancy (55.25%), followed by intrahepatic cholestasis in pregnancy (23.91%). Acute viral hepatitis was present in 8% patients. In 39% patients, preterm delivery was documented about 43.7% babies had birth weight less than 2.5 kg. Maternal mortality was 15.3% and perinatal mortality was 24.7%. Conclusions: Deranged liver function in pregnancy is associated with significant maternal and perinatal morbidity. Early diagnosis and appropriate intervention can improve feto-maternal outcome.